(untitled) (Delta Medical College Journal, 2020)
Background: Suicide is one of the commonest causes of death worldwide and has a great public health effect. The cause of suicide is found to be multi-factorial in which biological, psychological, social and environmental factors act together. The choice of method depends on the accessibility and availability of the means on the spot at the time of act. Objective: To find out the choice of ligature material used by the victims, type of hanging in relation to the point of suspension and other related factors. Materials and method: This retrospective observational study summarizes the post mortem examinations on 187 cases of suicide by hanging during January 2012 to December 2013 in the Department of Forensic Medicine, Sir Salimullah Medical College and Mitford Hospital, Dhaka, Bangladesh. Ligature material used by the victim was noted from the available forensic reports. Results: The current study is done to find out the commonly used material in cases of hanging. Male (63%) outnumbered females (37%) in committing suicide by hanging. Most commonly used ligature material was rope (28%) followed by ‘orna’/’dupatta’ (22%). The nature of ligature material was soft in 68% cases while hard material was used in 5% cases. The position of knot was observed on left side of neck in 63% cases followed by right side in 21% cases. The commonly used ligature was a rope with guider, and ceiling fan and tree branches as the point of suspension. Conclusion: Rope is frequently used for domestic purposes and thus it is also the most commonly used ligature material. Social, cultural and economic values must be strengthened to reduce incidence of suicide. Delta Med Col J. Jul 2019 7(2): 66-70